Impacto del “Proyecto Interdisciplinario de Atención de la Salud”, en la población de Tacares, Grecia 2004-2008 - Campos Arias, Flor de María (2012)
This article is a report of the activities developed in the “Interdisciplinary Health Care Project” involving the population of Tacares, Grecia through five years of interaction in this field. The objective is to address the health-disease process from an integral perspective, as an alternative model of transdisciplinary work based on an educational strategy framework promoting health and disease prevention by controlling the risk factors. The community of Tacares; received a life-cycle approach by providing attention to the infant since before its birth through Prenatal Monitoring, and the “Healthy Child Control Program” offered by the Caja Costarricense del Seguro Social (CCSS) (Social Security Institute of Costa Rica); and, preschool children from the local Education and Nutrition Center were included. The attention to pre-school children who attend educational centers from Tacares Norte, Tacares Sur, and Cataluña (all these places in Grecia) has been systematized. Moreover, students of the University of Costa Rica, who have scholarships of levels 10 and 11 (the highest scholarship categories) received attention, as did those citizens that are covered by “The Orthodontic Community Program”, the senior citizens who attend daytime care centers, as well as those elders who reside in nursing homes. As a result of this interdisciplinary Project effort, several health fairs and other educational activities were developed for health promotion in the area of Tacares Sur. Some other activities were workshops to teach how to make holders for tooth brushes and dispensers of dental floss (made of burlap bags) by utilizing disposable plastic bottles, oral dental bacterial controls were taken into account for those who needed them, as well as instructions were provided for a more effective oral hygiene, laboratory analysis of drinkable water were carried out, risk factors for oral disease were identified, and some women were trained for self- breast testing for early detection of breast cancer. The offered attention included dental care in general, community orthodontics, periodontics and oral surgery.The project was conducted in collaboration with CCSS, MEP (Ministry of Public Education), Ministry of Health (Ministry of Public Health and Social Services), the ASADAS (water and sewer local Associations), all of them dedicated to setting up a health system based on the home, the community and the working environment through University communal work, under the Vice- Rectory of Social Action of the University of Costa Rica.